2007
DOI: 10.2139/ssrn.1129780
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Alternative Procedures for the Selection of the Private Partner in PPP Projects

Abstract: In this work we compare three alternative procedures aimed at selecting a private partner in PPP projects: i.e. negotiation, auction and competitive negotiation. We show how the suitability of each of these selection mechanisms depends on many economic and institutional factors: e.g. the extent of contractual complexity, the degree of heterogeneity in firm costs, the level of competition, the probability of corruption. The main lesson of the paper is that the adoption of competitive negotiation can improve pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 14 publications
0
7
0
1
Order By: Relevance
“…Engel, Fischer and Galetovic (2006) study the rationale for private finance in PPPs. 24 They showed that private finance cannot be a means to save on distortionary taxation. Any additional $1 invested by the contractor saves society distortionary taxes but the concessionaire must be compensated for the additional investment through a longer contract term and this costs society future distortionary taxes equal to the initial tax saving.…”
Section: Private Finance Initiativementioning
confidence: 99%
See 2 more Smart Citations
“…Engel, Fischer and Galetovic (2006) study the rationale for private finance in PPPs. 24 They showed that private finance cannot be a means to save on distortionary taxation. Any additional $1 invested by the contractor saves society distortionary taxes but the concessionaire must be compensated for the additional investment through a longer contract term and this costs society future distortionary taxes equal to the initial tax saving.…”
Section: Private Finance Initiativementioning
confidence: 99%
“…The private finance aspect of PPPs has allowed the public sector to finance the construction of infrastructure "off the balance sheet" and to accelerate delivery of projects 24 See also the informal discussion in De Bettignies and Ross (2004).…”
Section: Private Finance Initiativementioning
confidence: 99%
See 1 more Smart Citation
“…According to Saussier et al [25], Public-Private Agreement (where PPP is considered as an example), a final negotiation phase after the tender evaluation is useful because it allows joining the flexibility needed in such a rigorous and challenging project given the tendering mechanism. Doni [12] looked at three kinds of tendering procedures, which are the negotiation, the auction, and the competitive negotiation procedure to provide contracting authorities with guidelines to follow for designing PPP/PFI tenders. In the absence of consent between one bidder and the public sector, the competitive negotiation will give a higher expected value to the government compared to other methods.…”
Section: Fig 2 Process Flow Of Ppp/pfi Projects (3pu/ukas 2010)mentioning
confidence: 99%
“…When awarding public-private agreements, the challenge is to find a way to combine the benefits of competition induced by auctions with the need for flexibility allowed by negotiation. The "competitive dialogue" procedure recently introduced in European regulation might be a way to go further in this direction (Doni 2007).…”
Section: The Information Structurementioning
confidence: 99%